Penerapan Model Pembelajaran Cooperative Learning Tipe Round Club pada Pembelajaran Akidah Akhlak untuk Meningkatkan Hasil Belajar Peserta Didik Kelas IV MI DDI 1 Palopo - Wanda Permatasari; Nur Fakhrunnisaa; Bustanul Iman RN (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to improve student learning outcomes through the implementation of the round club type cooperative learning model in the subject of Aqidah Akhlak, grade IV MI DDI 1 Palopo. The research method used is Classroom Action Research (CAR) which is implemented in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The research method used is Classroom Action Research (CAR) which is implemented in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study were 28 students. Data collection techniques were carried out through observation, student learning outcome tests, and documentation. The results of the study showed an increase in student learning outcomes after the implementation of the round club type cooperative learning model. In the first cycle, the average score was 69 with a learning completeness of 43%, then increased in the second cycle with an average score of 82 and a learning completeness reaching 82.14%. In addition, student learning activities became more active, able to work together, and more confident. Thus, the round club learning model has proven effective in improving student learning outcomes in the subject of Aqidah and Akhlak. This study was limited by the number of subjects and the scope of only one class, so the results cannot be widely generalized. Therefore, it is recommended that further research be conducted on a larger number of subjects and diverse materials to obtain more comprehensive results.